A SARS-CoV-2 vaccine candidate: In-silico cloning and validation. (2020) - Bhattacharya, Manojit; Sharma, Ashish Ranjan; Patra, Prasanta; Ghosh, Pratik; Sharma, Garima; Patra, Bidhan Chandra; Saha, Rudra P.; Lee, Sang-Soo; Chakraborty, Chiranjib
Abstract: SARS-CoV-2 is spreading globally at a rapid pace. To contain its spread and prevent further fatalities, the development of a vaccine against SARS-CoV-2 is an urgent prerequisite. Thus, in this article, by utilizing the in-silico approach, a vaccine candidate for SARS-CoV-2 has been proposed. Moreover, the effectiveness and safety measures of our proposed epitopic vaccine candidate have been evaluated by in-silico tools and servers (AllerTOP and AllergenFP servers). We observed that the vaccine candidate has no allergenicity and successfully combined with Toll-like receptor (TLR) protein to elicit an inflammatory immune response. Stable, functional mobility of the vaccine-TLR protein binding interface was confirmed by the Normal Mode Analysis. The in-silico cloning model demonstrated the efficacy of the construct vaccine along with the identified epitopes against SARS-CoV-2. Taken together, our proposed in-silico vaccine candidate has potent efficacy against COVID-19 infection, and successive research work might validate its effectiveness in in vitro and in vivo models. Highlights: In-silico cloning of peptide based vaccine candidate SARS-CoV-2. Validation of vaccine construct through computational biology. Proposed In-silico vaccine construct help to develop vaccine against COVID-19.